Non-English Students' English Learning Motivation - Khusaini, Fakhri (Lembaga Penelitian dan Pendidikan Mandala, 2023)
English is very important to learn by students in all majors, but students in two non-English majors in Bima town rarely attend English meeting held in campus. Therefore, this research was conducted to find out how non-English students' motivation to learn English is. This research used a qualitative descriptive method using an instrument in the form of a motivation questionnaire. The research results showed that non-English students have high motivation in learning English.